First, we divide the polynomial using long division:
................. x² - 4x + (8-k)
x² - 2x + k|x⁴ - 6x³ + 16x² - 25x + 10
................. x⁴ - 2x³ + kx²
................. -------------------------------
...................... -4x³ + (16-k)x² -25x
...................... -4x³ + 8x² ....... -4kx
...................... ---------------------------
...................... ......... (8-k)x² - (25-4k)x + 10
..................... .......... (8-k)x² - (16-2k)x + (8k-k²)
..................... .......... ------------------------------------
..................... ....................... - (9-2k)x + 10-8k+k²
So the remainder is - (9-2k)x + 10-8k+k². Since we know the remainder is x+a, equating coefficients yields 1=-(9-2k) and a=10-8k-k². Solving the first equation yields k=5, and substituting that into the second equation yields a = 10-40+25 = -5
Check of solution: if we have done our computations correctly, then multiplying our quotient with the divisor and adding the remainder should yields the original dividend. So:
(x² - 2x + k) * (x² - 4x + (8-k)) + x + a
(x² - 2x + 5) * (x² - 4x + 3) + x - 5
(x⁴ - 2x³ + 5x² - 4x³ + 8x² - 20x + 3x² - 6x + 15) + x-5
x⁴ - 6x³ + 16x² - 26x + 15 + x - 5
x⁴ - 6x³ + 16x² - 25x + 10
Which is the original polynomial. So our calculations were correct, and we are done. k=5, a=-5.
2007-05-03 00:05:10
·
answer #1
·
answered by Pascal 7
·
1⤊
0⤋
Hi there,
From the given expressions, we have the following equation:
x^4 - 6x^3 + 16x^2 - 25x + 10 = P(x)*(x^2 - 2x + k) + (x + a)
Note that the left hand side is a polynomial of degree 4, and so the expression P(x)*(x^2 - 2x + k) should also be of degree 4. Therefore, we deduce that P(x) must be a polynomial of degree 2 or a quadratic trinomial.
Hence, we let P(x) = x^2 + nx + m for some unknown values n and m. Notice that x^2 term has a coefficient 1, since the coefficient of x^2 in (x^2 - 2x + k) is also 1 and the coefficient of x^4 in the expression (x^4 - 6x^3 + 16x^2 - 25x + 10) is also 1, which we deduced from comparing coefficients.
So we have:
x^4 - 6x^3 + 16x^2 - 25x + 10 = P(x)*(x^2 - 2x + k) + (x + a)
=>
x^4 - 6x^3 + 16x^2 - 25x + 10 = (x^2 + nx + m)*(x^2 - 2x + k) + (x + a)
=>
x^4 - 6x^3 + 16x^2 - 25x + 10 = x^4 + (n-2)x^3 + (m-2n+k)x^2 + (kn -2m + 1)x + (mk + a).
Next, we compare the coefficients of each term on both sides:
For x^3:
-6 = n-2
For x^2:
16 = m - 2n + k
For x:
-25 = kn -2m + 1
For 1:
10 = mk + a.
For x^3, we readily get n = -4. Hence, the other equations will reduce to:
[Eq#1]
16 = m - 2n + k >> 16 = m +8+k >> 8 = m + k.
[Eq#2]
-25 = kn -2m + 1 >> -26 = -4k - 2m >> 13 = 2k + m
[Eq#3]
10 = mk + a.
If we subtract Eq#1 from Eq#2, we readily get: k = 13-8 = 5.
Substituting k=5 back to either Eq#1 or E#2 we get m = 3.
Finally, substituting k=5 and m=3 to Eq#3, we have:
10 = mk + a
>>
10 = 3*5 + a
>>
a = -5
Looking back at the problem, thus we found k and a:
k = 5,
a = -5.
:)
2007-05-03 07:14:05
·
answer #2
·
answered by wala_lang 2
·
0⤊
0⤋
x^4 - 6x^3 + 16x^2 - 25x + 10 = (x^2+Cx+D)(x^2 - 2x + k) + (x+a)
so,
x^4 - 6x^3 + 16x^2 - 25x + 10 = x^4 + x^3(C-2) + x^2(k+D-2C) + x(Ck-2D+1) + (Dk+a)
you can the equate coefficients (or use an equivalent method)
x^3 term: C=-4
x^2 term: 16=k+D-2C, so, k+D = 8
x term: -25 = Ck-2D+1, so, 2k+D=13 , so, k=5 and D=3
constant term: 10=Dk+a, so, a=-5
answer: k = 5, a = -5
2007-05-03 07:11:58
·
answer #3
·
answered by tsunamijon 4
·
0⤊
0⤋